Theoretical Aspects of Formation of Slang of Football Fans (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Sport is rightfully considered a significant social phenomenon of the 21st century, a sociocultural phenomenon of a universal nature. Today, sport is in the sphere of interests of specialists in various scientific fields. An important place is occupied by linguistic research devoted to the specifics of the language of various sports. The article is devoted to the consideration of theoretical aspects of the formation of football fans' slang. It is indicated that the linguistic personality of a football fan has a number of specific features, which in modern conditions are most objectively represented in Internet forums and communities.